Laguerre Expansions of C-resolvent for uniformly bounded β−times Integrated C−regularized semigroups Functions - Youssef Bajjou,; Aziz Blali,; Abdelkhalek El Amrani, (Utilitas Mathematica, 2025)
The aim of this paper is to approximate the C-resolvent of uniformly bounded β−times integrated C−regularized semigroups function by the Laguerre series, recalling the notions and the results used.